Validating a Virtual Environment for Sexual Assault Victims. Issue 2 (19th April 2017) - Loranger, Claudie; Bouchard, Stéphane
Abstract : Virtual reality has shown promising results in the treatment of posttraumatic stress disorder (PTSD) for some traumatic experiences, but sexual assault has been understudied. One important question to address is the relevance and safety of a virtual environment (VE) allowing patients to be progressively exposed to a sexual assault scenario. The aim of this study was to validate such a VE. Thirty women (victims and nonvictims of sexual assault) were randomly assigned in a counter‐balanced order to 2 immersions in a virtual bar: a control scenario where the encounter with the aggressor does not lead to sexual assault and an experimental scenario where the participant is assaulted. Immersions were conducted in a fully immersive 6‐wall system. Questionnaires were administered and psychophysiological measures were recorded. No adverse events were reported during or after the immersions. Repeated‐measures analyses of covariance revealed a significant time effect and significantly more anxiety (Cohen's f = 0.41, large effect size) and negative affect (Cohen's f = 0.35, medium effect size) in the experimental scenario than in the control condition. Given the safety of the scenario and its potential to induce emotions, it can be further tested to document its usefulness with sexual assault victims who suffer from PTSD.